Intepretasi Ayat-ayat Teologis Muḥammad al-Shawkānī tentang Manusia, Wahyu, dan Iman - Abd Kholid (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2017)
The article examines the typological category of Muḥammad al-Shawkānī’s “theological product”, which cannot be categorized as a part of Sunnī. This view is held by Muḥammad Ḥusayn al-Dhahabī and Muḥammad ‘Alī Ayāzī. Al-Dhahabī concludes that al-Shawkānī’s theological thought is seen as being Sunnī, but his work, Fatḥ al-Qadīr, is classified as Zaydiyya. Ayāzī, on the other side, says that al-Shawkānī’s theology tends to be more similarly rational to Zaydiyya and Mu‘tazilah. The author seeks to discuss the issue by exploring al-Shawkānī’s interpretation of theological verses on free will, predestination, and the relevance of revelation and human’s ratio. This study finds that al-Shawkānī’s theological arguments tend to be closely similar to Ahl al-Sunnah’s theological doctrines compare to that of Mu‘tazilah and Zaydiyya, although he surroundedly grew up among the very rational Zaydiyya. It can be observed, for instance, in his view of human’s deeds, which clearly indicates him as having a close position to the thought of Māturidiyya Bukhāra. In terms of the relevance of human’s ratio and the function of revelation, al-Shawkānī’s theological arguments are harmonious with Ash‘ariyya’s ideology.